A new face by combined surgery for patients with complex dentofacial deformity - (:unkn) unknown (SPRINGER, 2007)
Background: This article aims to present and discuss 53 patients who received a new identity because of major changes to the face after treatment with bimaxillary osteotomy, concomitant maxillomalar augmentation, genioplasty, and rhinoplastic procedures for their complex dentofacial skeletal deformity and class 3 malocclusion. Methods: During a 12-year period (January 1993 to April 2005), more than 500 patients with dentofacial deformities and malocclusions have undergone orthognathic surgery performed by a team consisting of the same plastic surgeons and orthodontists. Among this group, 53 patients (30 women and 23 men) underwent surgery for both aesthetic and functional concerns. The mean patient age was 20.4 years (range, 17-28 years). All the patients were treated with bimaxillary osteotomy, concomitant maxillomalar augmentation, osseous genioplasty, and rhinoplastic procedures in the same session. The patients were followed 12 to 44 months by the plastic surgeon, and at least 1 year by the orthodontist. Results: There was no orthognathic relapse or other major complications requiring reoperation. There was prolonged nerve anesthesia or hypoesthesia that resolved within 6 months for 4 patients (7.5%), a short period of anesthesia or hypoesthesia that resolved within 4 weeks for 11 patients (20.7%), a wide alar base in 3 patients, and a slight deviation of the cartilage septum in 2 patients. Conclusion: In one session, five different procedures can be performed without any problem, each of which can produce major changes to the face while maintaining the whole facial harmony. The authors determined that these dramatic positive outcomes for the combined procedure can easily be tolerated and accepted by all their patients. However, the patients have had difficulty with their family or friends accepting their new appearance, and even have had to change their photos on identification cards. This is encouraging for the management of new patients in the future.
Keywords: bimaxillary osteotomy; complex dentofacial deformity; concomitant maxillomalar augmentation; genioplasty; rhinoplasty; ORTHOGNATHIC SURGERY; SOFT-TISSUE; 3-DIMENSIONAL ANALYSIS; FACIAL DISPROPORTION; SKELETAL; MAXILLARY; NASAL; LIP; RECONSTRUCTION; ADVANCEMENT